Atypical Presentation of Systemic Arthritis in a Toddler with Down Syndrome - Emily Worley; Weijie Li; Jordan T. Jones (Hindawi Limited, 2021)
Systemic juvenile idiopathic arthritis (sJIA) is a chronic, inflammatory disease of childhood, which is characterized by the combination of arthritis, serositis, daily, high-spiking fevers, and evanescent macular rash and can present with the life-threatening complication of macrophage activation syndrome (MAS). Children with Down syndrome (DS) have complex medical challenges related to abnormalities in their immune system, which can cause a broad spectrum of disease manifestations, which can occur atypically. Children with DS are at increased risk for arthritis and interstitial lung disease (ILD) associated with sJIA that has high mortality. This case report outlines an atypical presentation of sJIA in a 21-month-old male with DS in which fever was not part of the initial presentation of sJIA and then later developed MAS and ILD. Due to broad spectrum of disease and atypical presentation in children with DS, this case report was created to increase awareness of atypical presentations of rheumatic disease in children with DS.